Insight for sustainable supplemental irrigation development for cocoa in changing Ghana’s agroforestry landscapes - Tilahun, Seifu A.; Amponsah, Andoh; Atampugre, Gerald; Zemadim, Birhanu; Dembélé, Moctar; Darko, S.; Mabhaudhi, Tafadzwanashe; Cofie, Olufunke O. (Springer, 2025)
Cocoa production in Ghana faces challenges from climate change and land use dynamics, necessitating sustainable intensification through supplemental irrigation. However, the availability of water resources for irrigation remains underexplored in Ghana’s agroforestry landscapes. This study assesses the potential of water resources for irrigation and impacts of land use and climate changes in the moist semi-deciduous agroforestry-dominated Upper Offin basin. Using Landsat images, the study analyzed land use patterns, hydro-climatic trends (1981–2022), and water balance based on rainfall and evapotranspiration. Findings reveal that streamflow represents only 10% of average annual rainfall (1333 mm), with subsurface flow predominating. Annual actual evapotranspiration (AET) accounts for 85% of rainfall, while deep percolation offers additional water potential. Shallow groundwater could irrigate 10% of the area during the 5-month dry season, doubling with deep percolation. Land use changes threaten this potential, as forest areas declined while cropland and grassland expanded (2008–2021), associated highly with the alteration of water balance components. Although rainfall remained stable, rising temperatures could increase cocoa water demand. AET declined over time, correlating with FAO-WaPOR data, while streamflow increased during the observed period (1986–2012). The study recommends groundwater supplemental irrigation systems for sustainable cocoa farming in Ghana and similar agroforestry regions, addressing climate and land use challenges effectively.